ANALISIS PENGARUH INFLASI DALAM PENENTUAN NOMINAL UANG PANAI PADA MASYARAKAT BUGIS - Ahmad, Ahmad; Muhammad Said; Naharuddin SR; Minhajuddin Madi; Muh. Nur Hidayat (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2025)
The tradition of determining uang panai (bridal gift) in Bugis society has faced challenges due to economic pressures, particularly inflation, which impacts the nominal value and its cultural significance. This study aims to analyze the influence of inflation on the determination of uang panai nominal and its alignment with Islamic family law and humanitarian values. Employing a qualitative approach, data were collected through in-depth interviews with six informants (three Bugis families, one adat leader, and two religious figures) and participatory observation of five uang panai negotiations in Makassar and Bone from February to April 2025. Findings reveal that inflation (18.09% from 2019–2024) has driven a significant increase in uang panai nominal, reaching Rp70 million in Makassar, often exceeding economic capacity and shifting its meaning from a symbol of honor (siri’) to a financial burden. However, some communities show flexibility by adjusting nominals, using phased payments, or substituting with goods like gold, aligning with Islamic principles of ease (taysīr) and humanitarian values like family harmony (pacce).